Mangrove Sebagai Sumber Ide Penciptaan Motif Batik dan Pewarna Alam - Aryani, Faatin Adilah (Pusat Penerbitan LPPM ISI Bali, 2025)
This study aims to create hand-drawn batik motifs by exploring the local potential of the mangrove ecosystem in Kutawaru, Cilacap. Mangrove batik is a craft innovation that not only emphasizes visual aesthetics but also reflects the ecological and socio-economic values of the local community. Using a craft-based creative method that includes exploration, design, and realization, the core ideas for motif development are inspired by the characteristic flora and fauna of the mangrove area, such as Rhizopora plants, ibis birds, and mullet fish. In addition to serving as motif inspiration, mangrove plants are also utilized as sources of eco-friendly natural dyes. Dye extracted from the bark of Rhizopora, which contains tannins, is used as an alternative to synthetic dyes that can negatively impact the environment. The resulting batik works demonstrate that exploring local potential through a mangrove ecosystem approach can contribute to the development of innovative batik designs while also supporting environmental sustainability and the economic empowerment of the local community. This batik not only functions as a cultural product but also serves as a medium for education and environmental conservation. The motif design process involves studying the forms of mangrove plants and animals, which are then transformed into decorative batik patterns through a stylization approach. In addition, the use of natural dyes extracted from the bark of Rhizopora mangroves rich in tannins demonstrates the potential of mangrove plants as an environmentally friendly dye source. This offers an alternative to synthetic dyes, which are known to be harmful to the environment.